Effects of surface management on runoff and soil erosion from some plots at Mlingano, Tanzania - Ngatunga, E.L.N.; Lal, R.; Uriyo, A.P. (1984)
Effects of four soil management treatments on runoff and erosion were investigated for a Rhodic Ferralsol using 10m × 2m runoff plots established on natural slopes of 10, 19 and 22% at Mlingano, Tanzania. The soil management treatments studied were bare fallow, plowing, straw mulch at 6 ton/ha and natural grass cover. The annual soil loss respectively for 10, 19 and 22% slopes was 37.8, 92.8 and 88.2 ton ha−1 for bare fallow; 13.6, 37.9 and 23.5 ton ha−1 for plowed; 0.12, 0.19 and 0.18 ton/ha for mulched; and 0.08, 0.14 and 0.10 ton ha−1 for grass cover treatments. The soil erodibility factor (K) computed from the annual soil loss was 0.160, 0.153 and 0.121 for soils of 10, 19 and 22% slopes, respectively. The K factors estimated from the nomogram were 0.09, 0.085 and 0.110, respectively. Out of the 793 mm of rains received, the annual runoff loss, respectively, for 10, 19 and 22% slope was 11.9, 15.4 and 13.0% for bare fallow; 5.5, 7.4 and 5.1% for plowed; 0.7, 0.7 and 0.5% for mulched; and 0.2, 0.4 and 0.3% for grass cover treatment.